Inhibition of GluR Current in Microvilli of Sensory Neurons via Na+-Microdomain Coupling Among GluR, HCN Channel, and Na+/K+ Pump - Kawasaki, Yasuhiro; Saito, Mitsuru; Won, Jonghwa; Bae, Jin Young; Sato, Hajime; Toyoda, Hiroki; Kuramoto, Eriko; Kogo, Mikihiko; Tanaka, Takuma; Kaneko, Takeshi; Oh, Seog Bae; Bae, Yong Chul; et al. (Frontiers in Cellular Neuroscience, 2018)
Glutamatergic dendritic EPSPs evoked in cortical pyramidal neurons are depressed by activation of hyperpolarization-activated cyclic nucleotide-gated (HCN) channels expressed in dendritic spines. This depression has been attributed to shunting effects of HCN current (Ih) on input resistance or Ih deactivation. Primary sensory neurons in the rat mesencephalic trigeminal nucleus (MTN) have the somata covered by spine-like microvilli that express HCN channels. In rat MTN neurons, we demonstrated that Ih enhancement apparently diminished the glutamate receptor (GluR) current (IGluR) evoked by puff application of glutamate/AMPA and enhanced a transient outward current following IGluR (OT-IGluR). This suggests that some outward current opposes inward IGluR. The IGluR inhibition displayed a U-shaped voltage-dependence with a minimal inhibition around the resting membrane potential, suggesting that simple shunting effects or deactivation of Ih cannot explain the U-shaped voltage-dependence. Confocal imaging of Na+ revealed that GluR activation caused an accumulation of Na+ in the microvilli, which can cause a negative shift of the reversal potential for Ih (Eh). Taken together, it was suggested that IGluR evoked in MTN neurons is opposed by a transient decrease or increase in standing inward or outward Ih, respectively, both of which can be caused by negative shifts of Eh, as consistent with the U-shaped voltage-dependence of the IGluR inhibition and the OT-IGluR generation. An electron-microscopic immunohistochemical study revealed the colocalization of HCN channels and glutamatergic synapses in microvilli of MTN neurons, which would provide a morphological basis for the functional interaction between HCN and GluR channels. Mathematical modeling eliminated the possibilities of the involvements of Ih deactivation and/or shunting effect and supported the negative shift of Eh which causes the U-shaped voltage-dependent inhibition of IGluR.